The Metaphorical Brain - Vicky T. Lai (Frontiers Research Topics, 2016)
Metaphor has been an issue of intense research and debate for decades (see, for example [1]). Researchers in various disciplines, including linguistics, psychology, computer science, education, and philosophy have developed a variety of theories, and much progress has been made [2]. For one, metaphor is no longer considered a rhetorical flourish that is found mainly in literary texts. Rather, linguists have shown that metaphor is a pervasive phenomenon in everyday language, a major force in the development of new word meanings, and the source of at least some grammatical function words [3]. Indeed, one of the most influential theories of metaphor involves the suggestion that the frequency of metaphoric language results because cross-domain mappings are a major determinant in the organization of semantic memory, as cognitive and neural resources for dealing with concrete domains are recruited for the conceptualization of more abstract ones [4]. Researchers in cognitive neuroscience have explored whether particular kinds of brain damage are associated with metaphor production and comprehension deficits, and whether similar brain regions are recruited when healthy adults understand the literal and metaphorical meanings of the same words (see [5] for a review). Whereas early research on this topic focused on the issue of the role of hemispheric asymmetry in the comprehension and production of metaphors [6], in recent years cognitive neuroscientists have argued that metaphor is not a monolithic category, and that metaphor processing varies as a function of numerous factors, including the novelty or conventionality of a particular metaphoric expression, its part of speech, and the extent of contextual support for the metaphoric meaning (see, e.g., [7], [8], [9]). Moreover, recent developments in cognitive neuroscience point to a sensorimotor basis for many concrete concepts, and raise the issue of whether these mechanisms are ever recruited to process more abstract concepts [10]. This Frontiers Research Topic brings together contributions from researchers in cognitive neuroscience whose work involves the study of metaphor in language and thought in order to promote the development of the neuroscientific investigation of metaphor. Adopting an interdisciplinary perspective, it synthesizes current findings on the cognitive neuroscience of metaphor, provides a forum for voicing novel perspectives, and promotes avenues for new research on the metaphorical brain.